Instagram content management strategy of the digital business study program to increase the number of visitors - Hana Nafisah; Abel Gandhy; Dewi Taurusyanti (Institute of Computer Science (IOCS), 2026)
Instagram has become an important medium for academic communication, promotion, and institutional branding in higher education. This study aims to analyze the Instagram content management strategy of the Digital Business Study Program of Universitas Pakuan using the Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal–External (IE), and SWOT approaches. A mixed-method approach was employed through interviews with three purposively selected informants, observations, and Instagram Insight documentation. Data validity was ensured through source triangulation. The findings indicate an IFE score of 3.12 and an EFE score of 3.22, positioning the study program in the Grow and Build category. The SWOT analysis identified the Strengths–Opportunities (SO) strategy as the most appropriate alternative, including optimizing Reels, increasing student activity publications, utilizing digital trends, and maintaining content consistency. This study contributes to strategic social media management and provides practical recommendations for improving audience engagement, institutional branding, and digital communication in higher education.